The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.bpj.2010.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Membrane Elastic Energy to Rhodopsin Function

Abstract: We considered the issue of whether shifts in the metarhodopsin I (MI)-metarhodopsin II (MII) equilibrium from lipid composition are fully explicable by differences in bilayer curvature elastic stress. A series of six lipids with known spontaneous radii of monolayer curvature and bending elastic moduli were added at increasing concentrations to the matrix lipid 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and the MI-MII equilibrium measured by flash photolysis followed by recording UV-vis spectra. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 37 publications
8
113
1
Order By: Relevance
“…Phosphatidylethanolamine-containing species in particular have strongly conical shapes and create headgroup packing defects and negative curvature stress in the context of bilayer-promoting lipids (Tate and Gruner, 1987;Rajamoorthi et al, 2005;Wassall and Stillwell, 2008). The major species of conical lipids in each mixture we used (DOPE in dioleoyl disk-mix and 22:6-18:0 PE in native OS lipids) have relatively similar shapes, as indicated by their identical spontaneous intrinsic curvature values (Soubias et al, 2010). We therefore suspect that differences in the extent of disorder in their acyl chains might account for the difference in their interactions with CTER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatidylethanolamine-containing species in particular have strongly conical shapes and create headgroup packing defects and negative curvature stress in the context of bilayer-promoting lipids (Tate and Gruner, 1987;Rajamoorthi et al, 2005;Wassall and Stillwell, 2008). The major species of conical lipids in each mixture we used (DOPE in dioleoyl disk-mix and 22:6-18:0 PE in native OS lipids) have relatively similar shapes, as indicated by their identical spontaneous intrinsic curvature values (Soubias et al, 2010). We therefore suspect that differences in the extent of disorder in their acyl chains might account for the difference in their interactions with CTER.…”
Section: Discussionmentioning
confidence: 99%
“…Neutral dioleoyl disk-mix liposomes contained DOPC, DOPE and cholesterol in a 6:4:1 molar ratio. These lipids possess no surface charge at neutral pH, but retain the lipid disorder and headgroup packing defects characteristic of dioleoyl polyunsaturated phospholipids (Soubias et al, 2010;Strandberg et al, 2012). A phospholipid extract of bovine ROS was prepared by organic extraction (Folch et al, 1957), using ,10 mg of bovine ROS purified as described (Papermaster, 1982).…”
Section: Liposome Production and Remodelingmentioning
confidence: 99%
“…The first is through changes in the physical properties of the bilayer, such as in terms of membrane fluidity, curvature, or stress, such that the conformational landscape of a given GPCR is indirectly modulated. This has been best demonstrated in studies of rhodopsin, where the transition between the metarhodopsin I and II states can be substantially influenced by the physical properties of the membrane (Mitchell et al, 1990;Botelho et al, 2002;Soubias et al, 2010). The second mechanism by which lipids influence GPCR activity is via their ability to contribute to the subcellular compartmentalization of the receptor and associated effector molecules in highly ordered domains, such as caveolae and lipid rafts (Chini and Parenti, 2004;Ostrom and Insel, 2004;Patel et al, 2008).…”
Section: Lipids As Allosteric Modulatorsmentioning
confidence: 99%
“…In the case of rhodopsin, the rhodopsin-membrane environment preferentially accommodates lipids with a PE head group and docosahexanoyl acyl (DHA) tail groups, which introduces a negative intrinsic curvature into the bilayer. Experimental studies have shown that rhodopsin is stabilized by establishing hydrogen bonds with the PE head group and that the transition between different conformational states of rhodopsin is influenced by the headgroup (Botelho et al, 2006;Soubias et al, 2010). Simulations have shown that polyunsaturated DHA tails modulate the direct protein-lipid interactions (Feller et al, 2003;Grossfield et al, 2006).…”
Section: Site-specific Interactionsmentioning
confidence: 99%
“…long-range lipid-protein interactions) can affect membrane protein folding, stability, and the ability to transition between conformations. The importance of membrane intrinsic curvature on protein function has been shown to be especially true in the case of GPCR proteins (Botelho et al, 2006;Soubias et al, 2010).…”
Section: Biological Membranesmentioning
confidence: 99%